IMPROVING READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMA NEGERI 16 BULUKUMBA THROUGH RECIPROCAL TEACHING TECHNIQUE. - Ahmad Arkam Ramadhani (-)
This research aimed at finding out whether or not Reciprocal Teaching Technique is effective to know the students’ ability reading comprehension.Pre-experimental method was applied in this research with one group pretest and posttest. The instrument of this research was reading comprehension test that consisted of 40 items in two components, namely 10 items for vocabulary and 30 items for reading comprehension test. The population of this research was the second grade students of SMA Negeri 16 Bulukumba district bontobahari  , academic year 2016/2017. The taken randomly total sample of this research consisted of 30 students from classThe result of this research showed that the second year students of SMA  Negeri 16 Bulukumba disctrict Bontobahari have fairly good score on the pretest with the mean score 7.58 then get improve to excellent score on the posttest with the mean sore 8.01. The data were analyzed by using t-test showed that the value of the t-test 12.5 is greater that the value of the t-table 2.045. It indicated that the Alternative Hypothesis (H1) was accepted and the Null Hypothesis (H0) was rejected. Thus it can be concluded that the use of reciprocal teaching technique is effective in improving the students’ reading comprehension.